Nasal-temporal asymmetric changes in retinal peripheral refractive error in myopic adolescents induced by overnight orthokeratology lenses - Chen, Xiaohang; Xiong, Yan; Qi, Xinzhou; Liu, Longqian (Frontiers in Neurology, 2023)
Objective To observe the changes in peripheral refraction in myopic adolescents after overnight orthokeratology and its influencing factors. Methods This was a prospective study among young myopic adolescents aged 8–14 years (n = 21). The peripheral refraction of the subjects was measured at 5, 10, 15, 20, 25, and 30° from the nasal and temporal side to the central fixation by WAM-5500 Open-field refractometer. The axial length, baseline spherical equivalent refraction, and other parameters were measured. The data were measured at baseline and 1, 3, and 12 months after wearing orthokeratology lenses. Results The relative peripheral refraction at the nasal and temporal side from central to 30° eccentricity revealed relative hyperopic defocus in all subjects at baseline measurement. One month after wearing the orthokeratology lenses, the relative peripheral refraction changed to myopic defocus, the nasal-temporal relative peripheral refraction was asymmetric, and the observed difference was statistically significant. Positive correlations were found between the change amount of nasal relative peripheral refraction and baseline spherical equivalent refraction, the baseline nasal relative peripheral refraction was higher than that on the temporal side, and after orthokeratology, the value of nasal relative peripheral refraction was lower than that on the temporal side. The changes at 30° on both sides were correlated to the axial elongation (rNasal = 0.565, rTemporal = 0.526, p < 0.05). Conclusion This study demonstrated that after orthokeratology, relative peripheral hyperopia in the myopic patients turned into relative peripheral myopia, and the nasal-temporal asymmetry changed significantly after orthokeratology, which was correlated with the baseline refractive state.